2009
DOI: 10.1007/s11845-009-0315-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum vascular endothelial growth factor and angiogenesis are related to the prognosis of patients with gastrointestinal stromal tumors

Abstract: SVEGF and VEGF show a correlation with poor prognosis of GIST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The role of VEGF in KIT mutant GIST has not been established. In a small study by Wang et al, serum vascular endothelial growth factor (VEGF) levels were higher in the high-risk GIST patients [10]. Another study showed a positive correlation between high VEGF expression and poor survival independent by KIT genotype [11].…”
Section: Discussionmentioning
confidence: 98%
“…The role of VEGF in KIT mutant GIST has not been established. In a small study by Wang et al, serum vascular endothelial growth factor (VEGF) levels were higher in the high-risk GIST patients [10]. Another study showed a positive correlation between high VEGF expression and poor survival independent by KIT genotype [11].…”
Section: Discussionmentioning
confidence: 98%
“…Prognosis was significantly poorer in patients with tumors expressing VEGF than in patients with tumors lacking VEGF expression [15]. The MVD and VEGF of GIST were higher than the MVD and VEGF of controls, and VEGF positivity showed a correlation with poor prognosis of GIST [12]. Patients with GIST expressing high VEGF had shorter median progression-free survival and median overall survival than did those with weak expression or non-expression of VEGF [34].…”
Section: Discussionmentioning
confidence: 91%
“…In our previous study, the expression of VEGF and MVD were greater in the GIST group than in the control group. Greater intensity of staining of VEGF and MVD was associated with more rapid progression and shorter survival in patients with GIST [12]. Chen et al [13] demonstrated that HIF-1alpha may play an important role in aggressive behavior and tumor angiogenesis in GIST, and high expression of HIF-1alpha was significantly correlated with tumor recurrence/distant metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also revealed significant negative correlation between serum VEGF levels and tumor VEGF expression and CD31-MVD (Iovino et al, n.d.). On the other hand, Wang et al, investigating gastrointestinal stromal tumors, found positive correlation between serum VEGF levels and tumor CD31-MVD (Wang et al, 2009b). Shimanuki et al, revealed direct relationship between serum VEGF levels and tumor CD34-MVD in nonsmall cell lung cancer (Shimanuki et al, n.d.).…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, including various human neoplasms (e.g. breast cancer, osteosarcoma, gastrointestinal stromal tumor), serum VEGF levels could accurately predict tissue VEGF expression and MVD (Iovino et al, n.d.;Chen et al, 2012;Wang et al, 2009a). However, there is lack of comprehensive studies concerning this issue in ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%